How to survive in a scale-up business : master the human skills needed to thrive in young, high-growth businesses - Murali, Vidya (Routledge, 2026)
Working in a scale-up is exciting, but it can also be exhausting. This book is your emotional survival kit for succeeding in a fast-paced and unpredictable environment.Scale-ups attract ambitious, driven and hardworking individuals seeking excitement, ownership, freedom and greater rewards. However, these opportunities often come with challenges. Understanding the emotional and behavioural patterns commonly seen in scale-ups - and learning from others' experiences - can help you move from struggling to thriving.In this book, author Vidya Murali brings together: A personal scale-up suitability checklist to help assess and understand whether scale-ups are the right environment for you based on your skills and preferences Guidance on what to look for when interviewing, and how to set yourself up for success in the first 90 days Insights, frameworks and coaching questions to tackle toxic patterns commonly seen in scale-ups Real-life case studies from scale-up leaders with lessons and strategies Practical strategies for introverts, highly sensitive people, ethnic minorities and people with ADHD and/or dyslexia to thrive in scale-ups Tools for building your emotional skills to progress and thrive in scale-ups - including if you lose your job or face a mental health breakdown A must-read for anyone transitioning into scale-ups or already working in one, this book will be of immense interest to graduates seeking their first full-time role, professionals transitioning from corporate environment, leaders - including founders - as well as HR professionals and coaches.
Keywords: New business enterprises.; Small business -- Growth.; Success in business.; Work environment.; elektronické knihy; electronic books